2010
DOI: 10.1371/journal.pone.0011857
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of Francisella novicida that Alter the Mechanism of Its Phagocytosis by Murine Macrophages

Abstract: Infection with the bacterial pathogen Francisella tularensis tularensis (F. tularensis) causes tularemia, a serious and debilitating disease. Francisella tularensis novicida strain U112 (abbreviated F. novicida), which is closely related to F. tularensis, is pathogenic for mice but not for man, making it an ideal model system for tularemia. Intracellular pathogens like Francisella inhibit the innate immune response, thereby avoiding immune recognition and death of the infected cell. Because activation of infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 47 publications
5
50
0
Order By: Relevance
“…Indeed, a study on Listeria monocytogenes has provided direct evidence in support of this hypothesis (65). Moreover, recent publications on F. tularensis have demonstrated enhanced inflammatory properties of several mutants, many of which appear to have cell wall defects (42,45,75). Thus, a straightforward explanation for the correlation between phagosomal escape and inflammasome activation may be that an increased number of bacteria in the cytoplasm will lead to more lysed bacteria as well.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, a study on Listeria monocytogenes has provided direct evidence in support of this hypothesis (65). Moreover, recent publications on F. tularensis have demonstrated enhanced inflammatory properties of several mutants, many of which appear to have cell wall defects (42,45,75). Thus, a straightforward explanation for the correlation between phagosomal escape and inflammasome activation may be that an increased number of bacteria in the cytoplasm will lead to more lysed bacteria as well.…”
Section: Discussionmentioning
confidence: 96%
“…To study the prerequisites of intracellular growth, we included the murine J774 macrophage-like cell line, since it has been widely used to investigate various aspects of L. monocytogenes and F. tularensis host cell infections in the past and therefore will serve as a comparison with previously published studies (14,(56)(57)(58)(59)(60)(61)(62)(63). The available evidence indicates, however, that J774 cells do not possess as potent an antimicrobial capacity as do various forms of primary macrophages (64), and in support of this view, we have previously observed that the ⌬iglI mutant replicated readily in J774 macrophages but not in BMDM (27).…”
Section: Requirement Of Fpi Proteins For Replication After Phagocyticmentioning
confidence: 99%
“…This observation suggests that although ⌬lpcC, ⌬manB, and ⌬manC are also defective in membrane components, the mechanism of cell killing may be different than the mutant strains studied by Peng et al (29). Also surprising was that ⌬lpcC, ⌬manB, and ⌬manC strains were phagocytosed at a much higher rate than WT F. novicida via a mechanism that does not require actin polymerization (34). Actin polymerization has thus far been demonstrated to be involved in internalization of Francisella by either phagocytic or endocytic pathways (21,22,35); therefore, the finding that ⌬lpcC, ⌬manB, and ⌬manC mutant strains are able to invade host cells independent of actin filaments remains to be understood.…”
mentioning
confidence: 87%
“…To identify genes that are involved in host immune evasion, we recently screened a comprehensive mutant library containing over 3000 F. novicida strains for mutants that were hypercytotoxic (34). Among the identified strains four F. novicida genes were involved in LPS core synthesis and assembly.…”
mentioning
confidence: 99%
See 1 more Smart Citation